(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Concurrently with the technological development that the world is witnessing the crime of money laundering to evolve faster and with multiple methods and its economic, political and social impacts raised increasingly. And for phenomenon dangerous the international community in recent years is keen to be considered combating money laundering as a general indication whereby verification of the international response the stats and its banks and financial institutions with international requirements mandated in this aspect, so the increasing interest the governments of countries in the laws and procedures that contribute to the reduction of the phenomenon of money laundering and avoid legislation economy and the banking and financial sectors, the negative results that can be exposed. The research aims to identify the phenomenon of money laundering and the statement of stages and methods and patterns of criminal and sources of funds, and the statement of the procedures followed in the banks to reduce this phenomenon, as well as to identify the role of control and administrative authorities and the statement of the supervisory role of the Central Bank and its importance as a supervisory and control the banks and compliance in commitment to those procedures set forth by the International Organization recommendations (FATF Financial Action Task Force on Money Laundering- ) and confirmed by the law No. (93) for the year 2004 to combat money laundering operations. The research aims to identify as well as the International Standards Organization (FATF) recommendations concerning the obligations of financial institutions.In order to achieve the goal of the research, engaged the a researcher earlier studies and books and resources related to the subject exposed the theoretical side, the practical side has included the preparation of a series of questions based on the anti-money international standards laundering law materials, have included a sample search (Rasheed Bank, Rafidain Bank, Bank Iraqi Middle East Investment Bank of Baghdad). With the development of a proposed program to audit procedures to reduce the phenomenon of money laundering in the Iraqi commercial banks.The research has reached a number of conclusions and recommendations that have been developed in the light of its contribution to the development of audit procedures to reduce the phenomenon of money laundering in commercial banks, to activate the role of the internal control systems and activation procedures to identify the customer and knowledge of his activities and the adoption of anti-money laundering policy based on Iraqi law No. (93) of the combating money laundering for the year 2004 as well as the international Standards Organization FATF and find ways that enable the combating money laundering and avoid its negative effects on financial institutions and thus the country’s economy.